Analysis of Completeness and Accuracy of PBL-Based Physics Module Materials in Simple Harmonic Motion - Febrianty, Wanda; Azizah, Syarifah Y Nur; Amalia, Tri Choirul Nur; Rahmat, Firdaus Nur; Muarifa, Ilahil Riska Dwi Aji; Rohkma, Risma Yusliqatur; Baros, Farid Denhar; Saragih, Ida Romauli; Mahardika, I Ketut; Subiki (International Journal of Educational Sciences and Development, 2023)
The development of a teaching module is carried out as a learning support medium, but in developing a teaching module it is necessary to analyze its completeness and accuracy. This study aimed to determine the validity of the PBL-based physics module on simple harmonic motion material that has been prepared. This type of research in this research was qualitative research. The data analysis method used in this research was descriptive analysis method. The data that had been obtained from the validation test in the form of a completeness and accuracy test of the material will be analyzed and described. In the PBL-based Physics module on simple harmonic motion material, a test was carried out with the validation of material experts obtained from the percentage value of the completeness aspect of the material by 87.5% and the accuracy of the material by 87.5%. These results were obtained using qualitative research methods that tend to use descriptive analysis. So that this module can be declared valid or can be used without revision.